Lifting removal of cationic dye (methylene blue) from wastewater by improving Zr-MOFs via second metal Al coordination - Naser Al Amery; Hussein Rasool Abid; Shaobin Wang; Shaomin Liu (Journal of Applied Materials and Technology, 2021)
Metal organic frameworks (MOFs) are frequently used as adsorbents in adsorption processes to remove dyes from effluent produced by the textile industry. Today, dye contaminants have become an important environmental problem. One of these dyes is methylene blue (MB) and its removal from wastewater is a priority because it is persistent and nondegradable. MB is used in many industries although it has potential harmful effects on human and aquatic life and can be considered a hazardous chemical when in wastewater. The present study shows the potential applications for enhanced forms of UiO-66 MOFs, such as UiO-66, UiO-66-10%Al and UiO-66-30%Al. These forms were prepared to remove MB from wastewater using batch experiments. Characterisation of adsorbents were accomplished successfully using Fourier transform infrared, X-ray powder diffraction, Brunauer–Emmett–Teller surface area and thermogravimetric analysis techniques. To investigate equilibrium adsorptive behaviour, Langmuir and Freundlich isotherm models were tested against the experimental data. Based on linear regression correlation coefficient (R2), the Freundlich model described the equilibrium isotherm of MOF/MB better than the Langmuir model. Of all forms of UiO-66 MOF, UiO-66-10%Al had the maximum Langmuir adsorption capacity at 49.26 mg/g. A kinetics study examined pseudo first-order, pseudo second order and Elovich models to determine which could explain the sorption mechanism. While the pseudo second order and Elovich models showed a good fit with the experimental data, the correlation coefficient of the pseudo second-order model was the highest. These results indicate that adsorption of MB is controlled by a chemisorption mechanism. Further, intraparticle diffusion was utilised to describe the adsorption mechanism and determine the rate-limiting steps in the adsorption process.